Prevalência de transtorno de ansiedade generalizada em idosos atendidos pela estratégia saúde da família do município de Porto Alegre - Menta, Caroline (2014)
Generalized Anxiety Disorder (GAD) is a common mental disorder that typically has an early age of onset, a chronic course, and a high degree of comorbidity with other anxiety and mood disorders. Despite the high prevalence of GAD in older adults, little is known about psychopathological features of excessive worry in the elderly. This is a cross-sectional study with a population-based sample of 578 individuals aged 60 years or more from the Family Health Strategy (FHS) of Porto Alegre, Brazil. Diagnosis were made by psychiatrists using the Mini International Neuropsychiatric Interview plus (MINIplus). The objective was evaluated a prevalence of GAD in elderly and to correlate association between GAD and sociodemographic and health characteristics. Total sample was characterized by: predominance of women (63.8%), younger elderly (62.4%), illiteracy or very poor schooling (61.6%), and low income rates (93.2%). The prevalence of GAD was 9% (IC:6.9-11.6). The main uncontrolled findings shows higher frequencies of GAD in female gender (10.8%,P.04), 60-69 age group (11%,P.047), not retired (14.7%,P.001), cohabitation with 4 or more people (11.9%,P.019), and history of falls (18.8%,P.003). Not being retired, history of falls, cohabitation with four or more people, heaving more than one hospitalization per year and poor self-perceived health presented significant association with GAD. This study presents associations with sociodemographic characteristics that weren´t examined previously in current literature and that should be further researched. Associations with gender, income and health open possibilities for new hypothesis tests in GAD or other anxiety disorders in elderly population in low income countries.